Traceability, value, and trust in the coffee market: A natural experiment in Ethiopia - Ludovic Mbakop; Glenn P. Jenkins; Leonard Leung; Kamil Sertoglu (Queen's University, Department of Economics, 2023)
This study measures the impact of traceability attributes on international buyers' willingness to pay for coffee produced in Ethiopia and the impact of accurate information on the production location of the coffee on the pricing according to its type and grade. Two sets of regressions models were used to investigate the important determinant factors affecting the export prices of trader and producer coffee, one each for trader and producer coffee, to measure the impact of the ECX on the prices and to evaluate the effect of the coffee types and grades on the prices. The results show that after coffee was forced to be traded via the ECX, traceable coffee export prices increased more than the reported price of non-traceable coffee. We also found that after the introduction of the ECX, the reported export prices of coffee were much more closely aligned to the movements in the international prices of coffee than before the ECX. Furthermore, we also find evidence that exporters and overseas buyers do not trust the results of the inspection and grading of coffee by the ECX unless traceability is also present. This is the first study to evaluate foreign buyers' willingness to pay for the attribute of traceability of Ethiopian coffee and to see how traceability has affected buyers' trust in the grades given by the ECX for the coffee it graded.
Keywords: D40; E23; Q17; 330; Ethiopian commodity exchange; Ethiopian coffee; Coffee traceability; Commoditization